2019
DOI: 10.18632/aging.101926
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Coenzyme Q10 content and oxidative status in human dermal fibroblasts using HMG-CoA reductase inhibitor over a broad range of concentrations. From mitohormesis to mitochondrial dysfunction and accelerated aging

Abstract: Coenzyme Q 10 (CoQ 10 ) is an endogenous lipophilic quinone, ubiquitous in biological membranes and endowed with antioxidant and bioenergetic properties, both crucial to the aging process. In fact, coenzyme Q 10 synthesis is known to decrease with age in different tissues including skin. Moreover, synthesis can be inhibited by 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase inhibitors such as statins, that are widely used hypochole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 68 publications
1
25
0
4
Order By: Relevance
“…CoQ10 is synthesized de novo by the mevalonate pathway and can be inhibited by 3-hydroxy-3-methyl-glutarylcoenzyme A (HMG-CoA) reductase inhibitors like statins. Marcheggiani et al 46 recently showed that statin mediated CoQ10 inhibition in human dermal fibroblasts triggered oxidative stress and mitochondrial dysfunction, and lead to premature "aging" of the cells in vitro.…”
Section: Chronological Skin Agingmentioning
confidence: 99%
“…CoQ10 is synthesized de novo by the mevalonate pathway and can be inhibited by 3-hydroxy-3-methyl-glutarylcoenzyme A (HMG-CoA) reductase inhibitors like statins. Marcheggiani et al 46 recently showed that statin mediated CoQ10 inhibition in human dermal fibroblasts triggered oxidative stress and mitochondrial dysfunction, and lead to premature "aging" of the cells in vitro.…”
Section: Chronological Skin Agingmentioning
confidence: 99%
“…Moreover, mitochondria-targeted agents, such as rotenone and metformin, also exhibit protective effects on cellular survival and extending lifespan at a low concentration via ROS-mediated mitohormetic signaling pathways (Yuyun et al 2012;De Haes et al 2014). This implied that mitochondria-targeted agents may produce a beneficial effect in aging-relative diseases via mitohormesis (Marcheggiani et al 2019;Bouitbir et al 2012;Liu et al 2019). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, mitochondria are central platforms to support cell function and maintain cell homeostasis. Given probable mitohormetic effect of drug related to low dosage, some mitochondria-targeted conventional drugs should be interrogated dialectically in clinic applications, such as statins (Marcheggiani et al 2019;Bouitbir et al 2012). Moreover, mitochondria-targeted agents, such as rotenone and metformin, also exhibit protective effects on cellular survival and extending lifespan at a low concentration via ROS-mediated mitohormetic signaling pathways (Yuyun et al 2012;De Haes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro studies have reported the effects of ALA in rat cell cultures [ 41 , 42 ] and CoQ10 in human cells [ 43 , 44 ], consistently showing decreased ROS production and inflammation, as well as an increase in thiol production and an improvement in ETC. Polyphenols can exert antioxidant or prooxidant effects depending on the oxygen and glucose levels used in the cell culture.…”
Section: Basic Research Studiesmentioning
confidence: 99%